2017
DOI: 10.15406/jpcpy.2017.07.00451
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Shyness and Maternal and Paternal Bonds across Adolescence

Abstract: Shyness has been defined as a tendency to feel anxious and to show inhibited behavior in interpersonal situations [8], for instance, to be afraid or experience discomfort upon meeting people. In particular, certain situations, such as interacting with authority figures, members of the opposite sex and strangers, are more likely to elicit shyness. Studies have also consistently found that shy people appear to be at risk for later maladjustment, such as psychological and social difficulties [9,10].In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results showed that 71.9% (64) were not seeking treatment. Only 9% (8) were seeking treatment and 19% (17) did not feel the need to seek treatment for anxiety. When asked about their willingness to seek treatment, 37.1% (33) were not willing to seek treatment, 38.2% (34) were willing to seek treatment and 24.7% (22) felt like they did not need treatment for anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that 71.9% (64) were not seeking treatment. Only 9% (8) were seeking treatment and 19% (17) did not feel the need to seek treatment for anxiety. When asked about their willingness to seek treatment, 37.1% (33) were not willing to seek treatment, 38.2% (34) were willing to seek treatment and 24.7% (22) felt like they did not need treatment for anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…From our study group, 8.3% of the students felt shy about sharing their problems with doctors. This may be a natural tendency or the result of inconsistent parenting, including being more overprotective, less warm, and supportive, and less encouraging of autonomy and independence (Lucia et al 2017). Inconsistent parenting can also lead to individuals bearing high levels of anxiety, as is proven by a study by Yose Yaffe, concluding that Parents with non-authoritative parenting styles (such as overprotective, authoritarian, and neglectful ones) who frequently use exaggerated (such as preventing autonomy), harsh, or inconsistent control are more likely to raise children and adolescents with anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%